Information and communication technologies (ict) in teaching the course of analytical chemistry - G. G. Melchenko; L. А. Ivanova; N. S. Golubeva (Высшее образование в России)
New theoretical and practical information concerning applying of ICT and multimedia technologies while teaching the course of analytical chemistry, is given in this article.